Neuropsychological decline up to 20 years before incident mild cognitive impairment - Caselli, Richard J. (Alzheimers Dement, 2020)
INTRODUCTION: Some Alzheimer disease biomarker studies found amyloid changes 20 years or more in advance of expected symptoms while cognitive changes lagged for over a decade, but this apparent lag might reflect the sensitivities of the biomarker and cognitive assays used. How far in advance of incident amnestic mild cognitive impairment (MCI) does cognition begin to decline? METHODS: Longitudinal neuropsychological study of an apolipoprotein E e4 enriched cohort of cognitively normal individuals at entry. Linear mixed models for MCI converters (n=65) and nonconverters (n=719) fitted for each neuropsychological measure; annual changes compared between groups before and after linear model intersections (inflection points). RESULTS: 34 of 35 cognitive measures and 9 of 18 behavioral measures declined faster post-inflection in the MCI converters; the earliest cognitive inflection point was nearly 20 years in advance of MCI diagnosis. DISCUSSION: The preclinical duration of cognitive and behavioral changes approaches the earliest reported biomarker changes.